Social Perception on New Normal (Case Study on Millennial Generations at North Sulawesi Indonesia) - Nikolas F. Wuryaningrat; Imam Alqurbani; Roy Mambu; Sjeddie R. Watung (Journal of International Conference Proceedings (JICP), 2021)
The purpose of this study is to explore the social perceptions of the millennial generation in implementing the adaptation of new habits during the Covid-19 pandemic. This research was conducted using descriptive quantitative research methods. The online survey was selected using the google form application. The data were taken from 400 respondents of State Higher Education (PTN) students in North Sulawesi as representatives of the millennial generation. The google form application is used to distribute questionnaires to target respondents. From the results of this survey, it can be explained that when the COVID-19 pandemic in the North Sulawesi millennial generation responded by perceiving several things that had been conveyed. Millennial generation respondents indicate that the level of millennial optimism for the sustainability of this life is well felt. Respondents positively respond to an optimistic attitude that routine millennial activities can still be carried out during the Covid-19 pandemic. Millennials in North Sulawesi also believe that the central and local governments can handle this pandemic.